The correlation between consumption levels of isoflavones and fiber sources with HbA1c levels in patients with type 2 diabetes mellitus at dr. H. Bob Bazar Hospital in South Lampung - Wahyu Nur Laily; Desti Ambar Wati; Riska Nur Suci Ayu; Amali Rica Pratiwi (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Diabetes mellitus is a metabolic disorder disease characterized by an increase in blood glucose levels due to a decrease in insulin secretion. Factors that can affect the patient's blood sugar level are the level of consumption of isoflavones and fiber. The purpose of this research is to determine the correlation between consumption levels of isoflavones and fiber sources with HbA1c levels in patients with type II diabetes mellitus at Dr. H. Bob Bazar Hospital in South Lampung. This research type is analytic with a cross-sectional approach. The sample in this research amounted to 45 patients with diabetes mellitus at Dr. H. Bob Bazar in South Lampung. The sampling used is purposive sampling. Primary data on the consumption of isoflavones and fiber that have been obtained by interview method with the SQ FFQ questionnaire and examination of HbA1c levels were then analyzed by using the Spearman Rank correlation statistical test. The results showed that there was a correlation between the level of consumption of isoflavone sources of food with HbA1c levels in the patients with type II DM (p-value 0.00) and there was a relationship between the level of consumption of dietary fiber sources with HbA1c levels in patients with type II DM at dr. H. Bob's Bazar (p-value 0.00).